Disinformation as a professional challenge of journalism and doumentation: Verificación de fuentes y contenidos - Montemayor-Rodríguez, Nancy; Torregrosa-Carmona, Juan-Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Fake news is not something new, but its current dimension is new, especially in the face of events of the importance of a global pandemic or a war, such as the one initiated by Putin in Ukraine in 2022. These realities and their informative dimension reinforce the idea that the dissemination of misleading content, if not directly false, is a constant throughout history, both in the public and social sphere and particularly in the space of the media, which requires new professional guidelines to verify facts and contents.